(untitled) (Journal of the College of Education for Women, 2018)
The basis of the personality of each individual lies in the early years of his or her life. If the personality of the child has been well organized and if the motives have been fully expressed and effectively directed, the child will have a strong will, happy self-confidence and a strong personality. If there is a failure In the early years, the individual will be unable to meet his responsibilities in life and may be the victim of many psychological disorders. The family is a learning process through which children acquire the customs, traditions, attitudes and values ​​prevailing in their social environment. (Pre-and-after) play and its relationship to parenting methods of (democratic-bullying-overprotection- and neglect), which will be addressed in the current study as to their effective role in raising or The study aims to measure self-confidence in pre-school children (before-and-after) play, to identify parenting methods by parents and kindergarten children by sex, and to reveal the correlation Between S And the level of self-confidence (before, during and after) play with kindergartens